2006
DOI: 10.1016/j.otohns.2005.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter Pylori and Laryngopharyngeal Reflux in Chronic Rhinosinusitis

Abstract: B-2b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Studies have indicated high prevalence of GERD in patients with chronic rhinosinusitis. In addition drug therapy of GERD together with antibiotics has improved symptoms of sinusitis in 79% of patients ( 11 ). Isolation of H. pylori from the respiratory and gastrointestinal tracts in several studies suggests that there may be a close relationship between H. pylori and pathogenesis of various ear, nose and throat problems ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated high prevalence of GERD in patients with chronic rhinosinusitis. In addition drug therapy of GERD together with antibiotics has improved symptoms of sinusitis in 79% of patients ( 11 ). Isolation of H. pylori from the respiratory and gastrointestinal tracts in several studies suggests that there may be a close relationship between H. pylori and pathogenesis of various ear, nose and throat problems ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since that time, the association of LPR with other medical conditions has been recognized. This association encompasses chronic pharyngitis [ 11 ], obstructive sleep apnea [ 12 ], chronic rhinosinusitis [ 13 15 ], and asthma [ 16 ]. Furthermore, the awareness of LPR as an airway disease has grown [ 3 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reflux was defined according to symptoms and signs, or pH study, or pepsin detection (Table 1). 4,8,10,16–29 There were 729 CRS patients (304 females), 187 suspected reflux patients, and 149 healthy individuals without reflux or CRS in the papers. Among studies, 47% of CRS patients were females ( N = 304/651).…”
Section: Resultsmentioning
confidence: 99%